No One Left Behind: Empowerment of Marginalized Community Through APPGM-SDG Solution Provider Projects - Sharifah, Syahirah; Mohamed Roseli, Nurul Rashidah; Sulaiman, Norhayati; Ahmad Zaini, Ahmad Fauzi; Abd. Rahim, Immie Rozainie; Abdul Rahman, Nurhidayah; Amat@Adnin, Norfarahin (Journal of Technical Education and Training, 2024)
Leaving no one behind is the main slogan of the Sustainable Development Goals (SDGs). It is easier to say than to achieve this slogan as marginalized groups are often left behind due to multiple barries and challenges i.e. geographical area, ethinicity, sex, socio-economic status and historical background. Through community programmes conducted by All Party Parliamentary Group Malaysia (APPGM-SDG), leaving no one behind is possible yet challenging. This article examines the impacts of twenty-three (23) APPGM-SDG programs in Perlis and Kedah. Data was collected through content analysis from solution providers’ proposal and reports, focus group discussions (FGD) and site visit. The findings indicate that 20 out of 23 programs delivered an impactful programs in four (4) domains- improvement in knowledge and motivation, the skills, networking and system. An important aspect of the program is that integrating of TVET into community programs is proving to be an important component in ensuring sustainable development and truly leaving no one behind.